Perkembangan penerbitan sukuk negara sebagai pembiayaan defisit fiskal dan kondisi ekonomi makro di Indonesia - Criseli, Audy Putri; Noor, Nabila Yatama; Yurike, Yurike; Panorama , Maya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The impact of the issuance of State sukuk as fiscal deficit financing and macroeconomic conditions on economic development in Indonesia. This study was conducted to determine the State sukuk into financing and macroeconomic conditions on the development of Islamic banking in Indonesia. The data used to conduct this research is a literature research analysis and is also complemented by some data derived from literature to be the origin of news seekers and data - data needed during this research. The results showed that the issuance of sukuk is subject to time limits. In accordance with the contract agreement, the sukuk issuer is obliged to provide returns, margins, or fees to sukuk holders as income and also repay sukuk funds at maturity. Sukuk serves as a means to help meet the country's financial needs, both in terms of the state budget and other needs. The presence of sukuk in Indonesia has the potential to support the nation's economy, given the significant impact that sukuk has on the state funding sector.